Nitrogen status in maize grown at different row spacings and nitrogen availability - Barbieri, Pablo Andres (2013)
Barbieri, P. A., Echeverría, H. E., Sainz Rozas, H. R. and Andrade, F. H. 2013. Nitrogen status in maize grown at differentrow spacings and nitrogen availability. Can. J. Plant Sci. 93: 10491058. Improving nitrogen use efficiency (NUE) isimperative to sustainable agriculture. To attain this goal in maize crops (Zea mays L.) there are nitrogen (N) diagnosismethods that enable determination of a crop?s nutritional status by analysis of plant parts. Maize planted in narrow rows(NR) can have increased dry matter (DM), grain yield and accumulated N. However, no reports have been found on theeffect of NR of N in plant diagnosis methods. An experiment was performed over 3 yr to evaluate NR and N fertilizer rateson the N dilution curve, N concentration in grain and chlorophyll content in maize. Treatments consisted of a factorialcombination of row width (70, 52 and 35 cm) and N rate (0 to 180 kg N ha1). The N dilution curves adjusted for fertilizedor control treatments were similar among row spacing. Nitrogen concentration in grain was correlated with relative yield(RY), and similar critical values for N response were similar between row spacings. Leaf chlorophyll content increasedwith N and NR; however, green index (GI) and N sufficiency index (NSI) values were not different between row spacingwhen correlated to RY. These results indicate that response thresholds to N fertilization determined on plant tissue for NRtreatments were similar among row spacings. Thus, there is no need to adjust the response thresholds to N applicationbased on row spacing, as NR did not cause any changes in physiological efficiency (PE) due to the determined proportionalincreases, both in accumulated N in DM and grain yield.